Wall flora of Edirne (Thrace Region) - (:unkn) unknown (My University, 2002)
Bu çalışmada, Edirne ili'nin (Türkiye'nin Trakya bölgesi) duvar florası (özellikle tarihi yapıların duvarlarında gelişenler) sunulmaktadır. Bu amaçla, Edirne'nin tarihi yapılarının duvarlarında yetişen taksonların tesbitiyle, Edirne florasına katkıda bulunulmuştur. Araştırma, 1999 yılı boyunca gerçekleştirilmiş ve 26 familya ve 61 cinse mensup toplam 99 takson ( 95 tür, 4 alttür) saptanmıştır. Bu taksonların 74'ü dikotil, 25'i ise, monokotildir. En yüksek sayıda taksona sahip olan familyalar; Poaceae (25 takson, % 25.2), Caryophyllaceae (10 taxon, % 10.1) ve Fabaceae (10 taxon, % 10.1)'dir. En yaygın olarakbulunan taksonlar ise, Stellaria media (L.) Vill. subsp. pallida (Dumort.) Aschers & Graebn. (Caryophyllaceae) (9 lokalitede), Parietaria judaica L. (Urticaceae) (8 lokalitede) ve Diplotaxis muralis (L.) DC. (Brassicaceae) (7 lokalitede)'dir. Kaydedilen taksonlar arasında, fitocoğrafik elementlerin yüzdesi değişmekte olup, şöyledir: Avrupa -Sibirya 12 takson (% 12.1); Akdeniz 2 takson (% 2.1); Doğu Akdeniz 4 takson (% 4.1); İran - Turan 3 takson (% 3.1) ve bilinmeyenler 73 takson (%73.8)'dur. Toplam taksonların 5'i (%5.1) kozmopolit, l ' i (% 1.1) ise, endemiktir. 11 taxon, Trakya bölgesi için yeni kayıttır.

The wall flora (especially plants growing on the walls of the historical buildings) of Edirne city (Thrace Region of Turkey) has been presented in this study. It was undertaken with the aim to determine the taxa growing on the walls of historical buildings of Edirne and make a contribution to the flora of Edirne. The study was carried out during the year 1999 and a total of 99 taxa (95 species, 4 subspecies) belonging to 61 genera and 26 families were recorded. 74 of these taxa belonged to Dicotyledons and 25 to Monocotyledons. The families with largest number of taxa were Poaceae(25 taxa, 25.2 %); Caryophyllaceae (10 taxa, 10.1 %); and Fabaceae (10 taxa, 10.1 %). The most widespread taxa were: Stellaria media (L.) Vill. subsp. pallida (Dumort.) Aschers & Graebn. (Caryophyllaceae) (in 9 localities), Parietaria judaica L. (Urticaceae) (in 8 localities) and Diplotaxis muralis (L.) DC. (Brassicaceae) (in 7 localities). The percentage of phytogeographical elements among the recorded taxa varied as follows; Euro - Siberian 12 taxa (12.1 %); Mediterranean 2 taxa (2.1 %); East Mediterranean 4 taxa (4.1 %); Irano - Turanian 3 taxa (3.1 %); unknown 73 taxa (73,8 %). 5 of total taxa (5,1 %) are cosmopolitan whilst 1 taxon(l,l %) is endemic. 11 taxa are new records for Thrace Region.
Edirne' nin (Trakya Bölgesi) duvar florası